Contemporary Jokes about Students: The Body of Texts and Their Genetic Relations - Anastasiya Astapova (Journal of Ethnology and Folkloristics)
In spite of the fact that so many papers in folklore scholarship have been dedicated to the question of the genesis of the joke as a genre (mainly speculating on its origin from the fairy tale) almost none of them attempts to reach beyond theoretical discussion on the problem. The aim of this article is to broaden the scope of existing research by analysing the genetic relations of contemporary jokes in a sample of Russian-language jokes about students collected from different sources (written, oral, Internet). Jokes about students are compared to jokes from other cycles and other genres with the help of statistical investigation. The types of genetic (and typological) relations between them are elucidated as well as the possible aspects of the origin of jokes.